An injectable, antibacterial, conductive hydrogel

CN116675879BActive Publication Date: 2026-10-09HEBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310678986.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2026-10-09
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

[0004]本发明的目的在于针对目前水凝胶功能单一的问题,提出一种可注射的抗菌、防污、导电水凝胶

Benefits of technology

[0026]The preparation method of this invention involves the free radical polymerization of zwitterions, N-haloamines, and acetals in a mixed solvent at 70°C to generate a ternary random copolymer. The generated polymer is then reacted overnight in an acidic solution at room temperature to generate acetal groups. The resulting polymer is dialyzed for three days, freeze-dried, and prepared into a 10% (w/w) solution with PBS for subsequent use. Alternatively, zwitterions, N-haloamines, and acrylic acid are reacted in deionized water at 70°C for 24 hours to generate a ternary random copolymer. ADH/EDC is added to the resulting ternary random copolymer solution, and the pH is adjusted to 4.75 to convert carboxylic acid groups to hydrazide groups. The resulting polymer is dialyzed in distilled water for three days, freeze-dried, and prepared into a 10% (w/w) solution with PBS for subsequent use. The resulting polymer solution is then injected using a double-barrel syringe to obtain a hydrogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116675879B_ABST
    Figure CN116675879B_ABST
Patent Text Reader

Abstract

The application discloses an injectable antibacterial and conductive hydrogel, which is composed of a polymer and a PBS solution, wherein the mass ratio of the polymer in the hydrogel is 5-20 wt%, and the mass ratio of the PBS solution in the hydrogel is 95-80 wt%; in the preparation, the injectable performance of the zwitterion and N-halamine hydrogel is realized by preparing the polymer with aldehyde groups and hydrazide groups through free radical copolymerization and by using the method that the aldehyde groups and the hydrazide groups can rapidly react to generate Schiff base bonds at room temperature. The hydrogel obtained by the application has the functions of antibiosis, conductivity and antifouling in addition to the good biocompatibility of the hydrogel. The structural formula of the polymer is as follows.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer technology and mainly relates to an injectable antibacterial and conductive hydrogel. Background Technology

[0002] Hydrogels are highly water-retaining polymer materials composed of hydrophilic polymers with a three-dimensional network structure. They possess water absorption, flexibility, good biocompatibility, and the ability to maintain a moist environment around wounds, making them widely used in tissue engineering, biomedical engineering, wound dressings, and electronic skin. In addition to these advantages, zwitterionic hydrogels also have the ability to prevent non-specific protein adsorption. However, simply preventing non-specific protein adhesion cannot completely solve the problem of biocontamination. The varying shapes of wound sites increasingly limit the application of ready-made hydrogels, and the complex healing process of wound sites necessitates a hydrogel that can convert changes in the wound site into electrical signals for timely detection. Therefore, the next generation of hydrogels should not only possess antifouling capabilities but also be injectable, antibacterial, and conductive.

[0003] In recent years, Schiff bases have been widely used in injectable hydrogels due to their mild reaction conditions, rapid reaction, and water as a byproduct. Yoyujing et al. (You,Y.; Xie,Y.; Jiang,Z., Injectable and biocompatible chitosan-alginic acid hydrogels. Biomedical Materials 2019,14(2),025010.) obtained dialdehyde alginate by treating alginate with periodic acid. The amino groups of chitosan and the aldehyde groups of alginate formed a hydrogel in situ through a Schiff base reaction, which exhibited good biocompatibility. Cao Jinying (Cao, J, Y.; Xiao, L.; Injectable drug-loaded polysaccharide hybrid hydrogels for hemostasis. RSC Advances 2019, 9, 36858-36866) developed a novel injectable drug-loaded hydrogel by forming Schiff base bonds using carboxymethyl chitosan (CMC), gelatin (GEL), and oxidized alginate (OSA). However, the presence of antibiotics can lead to bacterial resistance, necessitating the development of hydrogels with inherent antibacterial properties. Hydrogels with only antibacterial properties are functionally limited and cannot meet the demands of complex real-world environments. This paper presents a multifunctional antibacterial hydrogel that is injectable, antifouling, and conductive to address complex external environments. Summary of the Invention

[0004] The purpose of this invention is to address the current limitation of single-function hydrogels by proposing an injectable antibacterial, antifouling, and conductive hydrogel. This gel is composed of zwitterionic, N-haloamine, and Schiff base bonds. In its preparation, a polymer containing aldehyde and acylhydrazine groups is prepared via free radical copolymerization. The Schiff base bonds are rapidly generated at room temperature by the aldehyde and acylhydrazine groups, thus achieving the injectable properties of the zwitterionic, N-haloamine hydrogel. The hydrogel obtained by this invention, in addition to possessing the good biocompatibility inherent in hydrogels, also exhibits antibacterial, conductive, and antifouling functions.

[0005] The technical solution adopted by this invention to solve its technical problem is:

[0006] An injectable antibacterial, conductive hydrogel, comprising a polymer and a PBS solution; wherein the polymer accounts for 5-20 wt% of the hydrogel by mass, and the PBS solution accounts for 95-80 wt% of the hydrogel by mass.

[0007] The concentration of the PBS solution is 0.01-0.05M;

[0008] The structural formula of the polymer is as follows:

[0009]

[0010] In the structural formula, the wavy lines represent repeating basic units.

[0011] The method for preparing the injectable antibacterial and conductive hydrogel includes the following steps:

[0012] Polymer A and polymer B were dissolved separately in PBS solution to obtain 2.5-10 wt% polymer solutions. The two polymer solutions were then mixed, and the hydrogel was formed.

[0013] The mass ratio is: polymer A: polymer B = 1:1; the concentration of the PBS solution is 0.01-0.05M.

[0014] The structural formula of polymer A is: n=6-8; m=0.5-2; q=1-3;

[0015] The structural formula of the polymer B is: n = 3 - 5; m = 0.5 - 2;

[0016] The method for preparing polymer A includes the following steps:

[0017] Amphoteric ions, acetals, and N-haloamines are added to distilled water, nitrogen is bubbled through for 30–60 minutes, initiator AIBA is added, and the reaction is carried out at 65–75°C for 20–30 hours to obtain intermediate A. Intermediate A is added to NaClO solution and reacted for 1–3 hours, then dialyzed for 1–3 days to obtain intermediate B solution. Concentrated hydrochloric acid is added to intermediate B solution, and the reaction is carried out for 8–14 hours. The resulting reaction solution is dialyzed at room temperature for 2–3 days, and then freeze-dried to obtain polymer A.

[0018] The following ingredients are added to every 30 mL of distilled water: 1–5 g zwitterion, 0.5–1 g acetal, 0.2–0.8 g N-haloamine, 10–50 mg AIBA, 10–30 mL NaClO solution, and 1–3 mL concentrated hydrochloric acid; the molar ratio is N-haloamine:NaClO = 1:2.

[0019] The method for preparing polymer B includes the following steps:

[0020] Amphoteric acid and acrylic acid were added to distilled water, and nitrogen gas was introduced for 30-60 minutes. Initiator AIBA was added, and the reaction was carried out at 65-75°C for 20-30 hours. Then, ADH and EDC were added, and the reaction was carried out for 8-14 hours, during which the pH of the system was adjusted to maintain 4.7-4.8. The resulting reaction solution was then dialyzed at room temperature for 2-3 days, and after freeze-drying, polymer B was obtained.

[0021] For each 30 mL of distilled water, add 1–5 g of zwitterionic acid, 0.2–1 g of acrylic acid, and 20–60 mg of initiator; the molar ratio is ADH:acrylic acid = 2:1; EDC:acrylic acid = 2:1.

[0022] The NaClO solution is 1–10 wt%; the concentrated hydrochloric acid concentration is 6–12 M.

[0023] The zwitterion is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propionic acid)ammonium hydroxide; the acetal is N-(2,2-dimethoxyethyl)acrylamide; the N-haloamine is 5,5-dimethyl-3-(4-vinylbenzyl)imidazolidine-2,4-dione; ADH is adipate dihydrazide; and EDC is 1-ethyl-(3-dimethylaminopropyl)carbodiimide.

[0024] The initiator is azobisisobutyramidine hydrochloride.

[0025] The essential features of this invention are:

[0026] The preparation method of this invention involves the free radical polymerization of zwitterions, N-haloamines, and acetals in a mixed solvent at 70°C to generate a ternary random copolymer. The generated polymer is then reacted overnight in an acidic solution at room temperature to generate acetal groups. The resulting polymer is dialyzed for three days, freeze-dried, and prepared into a 10% (w / w) solution with PBS for subsequent use. Alternatively, zwitterions, N-haloamines, and acrylic acid are reacted in deionized water at 70°C for 24 hours to generate a ternary random copolymer. ADH / EDC is added to the resulting ternary random copolymer solution, and the pH is adjusted to 4.75 to convert carboxylic acid groups to hydrazide groups. The resulting polymer is dialyzed in distilled water for three days, freeze-dried, and prepared into a 10% (w / w) solution with PBS for subsequent use. The resulting polymer solution is then injected using a double-barrel syringe to obtain a hydrogel.

[0027] The beneficial effects of this invention are as follows:

[0028] 1. This invention introduces Schiff base bonds into the hydrogel, giving it the advantage of being injectable. The gelation time of the hydrogel at room temperature can reach about 2.90±0.51s.

[0029] 2. Zwitterions have been proven to be biocompatible substances. The introduction of zwitterions can endow hydrogels with good biocompatibility. In this invention, the survival rate of L929 cells after co-culturing the hydrogel precursor solution with the hydrogel for one day and three days was over 85%. In addition, zwitterions can also provide excellent antifouling properties for hydrogels by combining with water molecules to form a dense hydration layer. When we co-cultured different concentrations of BSA protein solutions with hydrogels, the zwitterion content of 80% could prevent the adhesion of 1000 μg / mL protein solution.

[0030] 3. N-Halamines have been proven by many researchers to have excellent antibacterial effects. The hydrogel prepared in this invention can effectively kill more than 90% of bacteria after co-culturing with Escherichia coli and Staphylococcus aureus for 1 hour.

[0031] 4. Because the zwitterions carry both positive and negative charges, and the solution for dissolving the prepolymer of the hydrogel is a PBS solution, which can provide free-moving ions for the hydrogel, this endows the hydrogel with conductive properties. The conductivity can reach up to 0.29 S / m after testing with an electrochemical workstation. Attached Figure Description

[0032] Figure 1 Schematic diagram of hydrogel; where -CH=N represents a Schiff base bond; This is due to electrostatic interaction; the translucent portion represents the water that has swollen within the hydrogel.

[0033] Figure 2 These are scanning electron microscope images of the hydrogels in Examples 6, 7, 8, and 9; where, Figure 2a is PSBMA / AD0; Figure 2 b represents PSBMA / AD 10 ; Figure 2 c represents PSBMA / AD 20 ; Figure 2 d is PSBMA / AD 30 ;

[0034] Figure 3 The figures shown are test results for the antifouling performance of the hydrogel in Examples 6, 7, 8, and 9. Figure 3 (a) shows the antifouling properties of the hydrogel against different concentrations of BSA protein; Figure 3 (b) Hydrogel PSBMA / AD0 and PSBMA / AD 30 Antifouling properties against Escherichia coli and Staphylococcus aureus

[0035] Figure 4 The figures show the antibacterial properties of the hydrogels in Examples 6, 7, 8, and 9. Figure 4 (a) Hydrogel against Staphylococcus aureus Figure 4 (b) shows the antibacterial properties of Escherichia coli. Detailed Implementation

[0036] A schematic diagram of the hydrogel obtained by this invention is shown below. Figure 1 As shown, the black lines constitute the polymer chain segment structure in the hydrogel, -CH=N and The electrostatic interaction between positive and negative charges constitutes the interaction force between polymer chain segments, and the surrounding water molecules are the water that swells in the hydrogel. Together, they constitute the structure and composition of the hydrogel.

[0037] Example 1:

[0038] Polymer A 10 Preparation

[0039] 4g of 3-((2-methacryloyloxy)ethyl)dimethylamino)propane-1-sulfonate (zwitterionic), 0.7093g of acetal, and 0.4987g of N-haloamine were dissolved in 30mL of distilled water and poured into a 250mL flask. Nitrogen gas was purged for 40 minutes, followed by the addition of 40mg of initiator AIBA and nitrogen preservation. The reaction was carried out at 70℃ for 24 hours. The reaction solution containing the polymer was then transferred to 20mL of 5wt% NaClO solution and reacted for 2 hours. The polymer solution was dialyzed against distilled water for two days using an MD3500 dialysis bag. The polymer solution obtained from the dialyze was poured into a beaker, and 2mL of 12mol / L HCl solution was added. The resulting polymer was dialyzed against room temperature for 3 days and then freeze-dried at -20℃ to obtain the target product polymer. The molar ratio of zwitterionic:N-haloamine:acetal was 7:1:2. Polymer A was thus obtained. 10 .

[0040]

[0041] L929 cells were counted using the CCK-8 cell counting kit to assess the cell compatibility of zwitterionic polymer precursors at different concentrations (1 μg / ml, 0.1 μg / ml, and 0.01 μg / ml). After incubation for 24 h and 72 h, the cell viability of all precursor polymers remained above 85%, indicating that the presence of ADMH did not introduce any additional toxicity at different polymer concentrations. These experimental results demonstrate that the hydrogel exhibits good biocompatibility and excellent antifouling properties, suggesting significant potential applications in biomaterials such as wound dressings.

[0042] Example 2:

[0043] Polymer A 20 Preparation

[0044] 4g of zwitterion (same as in Example 1, and the same for the following examples), 0.8257g of acetal, and 1.1712g of N-haloamine were dissolved in 30mL of distilled water and poured into a 250mL flask. Nitrogen gas was purged for 40 minutes, and 40mg of initiator AIBA was added. Nitrogen was then maintained, and the reaction was carried out at 70℃ for 24 hours. The reaction solution containing the polymer was then transferred to 20mL of 5wt% NaClO solution and reacted for 2 hours. The polymer solution was dialyzed against distilled water for two days using an MD3500 dialysis bag. The polymer solution obtained from the dialyze was poured into a beaker, and 2mL of 12mol / L HCl solution was added to the beaker. The resulting polymer was dialyzed against room temperature for 3 days and then freeze-dried at -20℃ to obtain the target product polymer. The molar ratio of zwitterion:N-haloamine:acetal was 6:2:2. Polymer A was thus obtained. 20 .

[0045] Example 3:

[0046] Polymer Preparation A 30

[0047] 4g of zwitterion, 0.9861g of acetal, and 2.0974g of N-haloamine were dissolved in 30mL of distilled water and poured into a 250mL flask. Nitrogen gas was purged for 40 minutes, followed by the addition of 40mg of initiator AIBA and nitrogen preservation. The reaction was carried out at 70℃ for 24 hours. The reaction solution containing the polymer was then transferred to 20mL of 5wt% NaClO solution and reacted for 2 hours. The polymer solution was dialyzed against distilled water for two days using an MD3500 dialysis bag. The polymer solution obtained from the dialyze was poured into a beaker, and 2mL of 12mol / L HCl solution was added. The resulting polymer was dialyzed against room temperature for 3 days and then freeze-dried at -20℃ to obtain the target product polymer. The molar ratio of zwitterion:N-haloamine:acetal was 5:3:2. Polymer A was thus obtained. 30 .

[0048] From Examples 1-3, we can obtain three polymers with different proportions of N-haloamines.

[0049] Example 4:

[0050] Preparation of polymer B

[0051] 4 g of zwitterion and 0.2580 g of acrylic acid (0.0036 mol) were dissolved in 30 mL of distilled water and poured into a 250 mL flask. Nitrogen gas was purged for 40 minutes, and 40 mg of initiator AIBA was added. The mixture was then kept under nitrogen and reacted at 70 °C for 24 hours. The polymer solution was then removed and 1.5678 g of ADH (0.0072 mol) and 1.7253 g of EDC (0.0072 mol) were added at room temperature. The reaction was carried out for 12 hours (to convert the carboxylic acid group to an acylhydrazide group). (The pH of the system was adjusted with 1 mol / L hydrochloric acid and maintained at 4.75 throughout the reaction). The resulting polymer was dialyzed at room temperature for 3 days and then lyophilized for later use. The synthetic route of the obtained polymer PSBMA / H is shown in the figure below, where the ratio of zwitterion to adipylhydrazide is 4:1.

[0052]

[0053] Example 5:

[0054] Preparation of polymer A0

[0055] 4g of zwitterion and 0.6183g of acetal were dissolved in 30mL of deionized water and poured into a 250mL flask. Nitrogen gas was bubbled through the flask for 40 minutes, and AIBA initiator was added to maintain nitrogen. The reaction was carried out in an oil bath at 70℃ for 24 hours. The reaction solution containing the polymer was then transferred to 20mL of 5wt% NaClO solution and reacted for 2 hours. The polymer solution was dialyzed against distilled water for two days using an MD3500 dialysis bag. The polymer solution obtained from the dialyze was poured into a beaker, and 2mL of 12mol / L HCl solution was added to the beaker. The resulting polymer was dialyzed against room temperature for 3 days and then freeze-dried at -20℃ to obtain the target product polymer. The molar ratio of zwitterion to acetal was 8:2. Polymer A0 was thus obtained.

[0056]

[0057] Example 6:

[0058] Preparation of hydrogel PSBMA / AD0

[0059] First, polymer B and polymer A0 were obtained using Examples 4 and 5;

[0060] In the second step, the hydrogel precursor polymers prepared in Examples 4 and 5 were dissolved in PBS solution to prepare polymer PSBMA / H solution and polymer PSBMA / A solution with a mass ratio of 10wt%. The two polymer solutions were mixed in equal volumes, and the resulting polymer solutions were gelled by mixing in about 3 seconds.

[0061] The scanning electron microscope (SEM) images of the PSBMA / AD0 hydrogel are shown in Figure (1), revealing a distinct three-dimensional pore structure. The antifouling performance of the hydrogel against proteins was characterized using BSA protein as a model protein, as shown in Figure (3). Even when co-cultured with a high concentration (1000 μg / mL) protein solution, the PSBMA / AD0 hydrogel could repel approximately 100% of the added BSA. The antifouling performance of the hydrogel against bacteria was characterized using Escherichia coli and Staphylococcus aureus as bacterial models, as shown in Figure (3). The removal rates of both Escherichia coli and Staphylococcus aureus exceeded 99%. The resistance of the hydrogel was measured using an electrochemical workstation and analyzed using the formula... The calculated conductivity of the hydrogel is shown in the figure, where the conductivity of PSBMA / AD0 is 0.11 S / m.

[0062] Example 7

[0063] Hydrogel PSBMA / AD 10 Preparation

[0064] The first step involves using polymers B and A prepared in Examples 1 and 4. 10 ;

[0065] In the second step, the hydrogel precursor polymers prepared in Examples 1 and 4 were dissolved in PBS solution to prepare a polymer solution with a mass ratio of 10 wt%. The polymer solutions prepared in Examples 4 and 5 were then mixed to form a gel.

[0066] The scanning electron microscope (SEM) images of the PSBMA / AD0 hydrogel are shown in Figure (1), revealing a distinct three-dimensional pore structure. The antifouling properties of the hydrogel against proteins were characterized using BSA protein as a model protein, as shown in Figure (3). When the protein concentration was ≤250 μg / mL, the hydrogel could repel ~100% of the added BSA. The resistance of the hydrogel was measured using an electrochemical workstation and analyzed using the formula... The calculated conductivity of the hydrogel is shown in the figure, where PSBMA / AD 10 The conductivity is 0.10 S / m. The antibacterial properties of the hydrogel were tested using Escherichia coli and Staphylococcus aureus as examples. The results are shown in Figure (4). After co-culturing with bacteria for 1 hour, the bactericidal rate against Escherichia coli and Staphylococcus aureus was only ~35%.

[0067] Example 8

[0068] Hydrogel PSBMA / AD 20 Preparation

[0069] The first step involves using polymers B and A prepared in Examples 2 and 4. 20 ;

[0070] In the second step, the hydrogel precursor polymers prepared in Examples 2 and 4 were dissolved in PBS solution to prepare a polymer solution with a mass ratio of 10 wt%. The polymer solutions prepared in Examples 4 and 5 were then mixed to form a gel.

[0071] The scanning electron microscope (SEM) images of the PSBMA / AD0 hydrogel are shown in Figure (1), revealing a distinct three-dimensional pore structure. The antifouling properties of the hydrogel against proteins were characterized using BSA protein as a model protein, as shown in Figure (3). When the protein concentration was ≤250 μg / mL, the hydrogel could repel ~100% added BSA. When the BSA protein concentration reached 500 μg / mL, the repulsion rate was 13.4%, and at a protein concentration of 1000 μg / mL, the repulsion rate was 17%. The resistance of the hydrogel was measured using an electrochemical workstation and analyzed using the formula... The calculated conductivity of the hydrogel is shown in the figure, where PSBMA / AD 20The conductivity is 0.09 S / m. The antibacterial properties of the hydrogel were tested using Escherichia coli and Staphylococcus aureus as examples. The results are shown in Figure (4). After co-culturing with bacteria for 1 h, the bactericidal rate against Escherichia coli and Staphylococcus aureus was ~90%.

[0072] Example 9

[0073] Hydrogel PSBMA / AD 30 Preparation

[0074] The first step involves using polymers B and A prepared in Examples 3 and 4. 30 ;

[0075] In the second step, the hydrogel precursor polymers prepared in Examples 3 and 4 were dissolved in PBS solution to prepare a polymer solution with a mass ratio of 10 wt%. The polymer solutions prepared in Examples 4 and 5 were then mixed to form a gel.

[0076] The scanning electron microscope (SEM) images of the PSBMA / AD0 hydrogel are shown in Figure (1), revealing a distinct three-dimensional pore structure. The antifouling properties of the hydrogel against proteins were characterized using BSA protein as a model protein, as shown in Figure (3). When the protein concentration was ≤250 μg / mL, the hydrogel could repel ~100% added BSA. When the BSA protein concentration reached 500 μg / mL, the repulsion rate was 21%, and at a protein concentration of 1000 μg / mL, the repulsion rate was 30.7%. The resistance of the hydrogel was measured using an electrochemical workstation and analyzed using the formula... The calculated conductivity of the hydrogel is shown in the figure, where PSBMA / AD 20 The conductivity is 0.08 S / m. The antibacterial properties of the hydrogel were tested using Escherichia coli and Staphylococcus aureus as examples. The results are shown in Figure (4). After co-culturing with bacteria for 1 h, the bactericidal rate against Escherichia coli and Staphylococcus aureus was ~90%.

[0077] Through Examples 7-9, we can see that as the content of N-haloamine increases, the antibacterial properties of the hydrosol of the present invention are greatly improved, indicating that the present invention has antibacterial properties.

[0078] Matters not covered in this invention are common knowledge.

Claims

1. A method for preparing an injectable antibacterial, conductive hydrogel, characterized in that the method includes the following steps: Polymer A and polymer B were dissolved in PBS solution to obtain 2.5-10 wt% polymer solutions respectively. The two polymer solutions were then mixed to obtain the hydrogel. The mass ratio is: polymer A: polymer B = 1:1; the concentration of the PBS solution is 0.01-0.05M. The structural formula of polymer A is: n=6-8; m=0.5-2; q=1-3; The structural formula of the polymer B is: a = 3 - 5; b = 0.5 - 2; The resulting hydrogel consists of a polymer and a PBS solution; wherein, The polymer accounts for 5-20 wt% of the hydrogel, and the PBS solution accounts for 95-80 wt% of the hydrogel.

2. The method for preparing the injectable antibacterial and conductive hydrogel as described in claim 1, characterized in that: The method for preparing polymer A includes the following steps: Amphoteric ions, N-(2,2-dimethoxyethyl)acrylamide, and 5,5-dimethyl-3-(4-vinylbenzyl)imidazolidine-2,4-dione were added to distilled water, and nitrogen gas was introduced for 30-60 minutes. Initiator AIBA was added, and the reaction was carried out at 65-75°C for 20-30 hours to obtain intermediate A. Intermediate A was added to NaClO solution and reacted for 1-3 hours, followed by dialyzing for 1-3 days to obtain intermediate B solution. Concentrated hydrochloric acid was added to intermediate B solution, and the reaction was carried out for 8-14 hours. The resulting reaction solution was dialyzed at room temperature for 2-3 days, and then freeze-dried to obtain polymer A. in, Add 1-5g zwitterion, 0.5-1g N-(2,2-dimethoxyethyl)acrylamide, 0.2-0.8g 5,5-dimethyl-3-(4-vinylbenzyl)imidazolidine-2,4-dione, 10-50mg AIBA, 10-30mL NaClO solution, and 1-3mL concentrated hydrochloric acid to every 30mL of distilled water; the molar ratio is 5,5-dimethyl-3-(4-vinylbenzyl)imidazolidine-2,4-dione:NaClO=1:

2. The method for preparing polymer B includes the following steps: Amphoteric acid and acrylic acid were added to distilled water, and nitrogen gas was introduced for 30-60 minutes. Initiator AIBA was added, and the reaction was carried out at 65-75°C for 20-30 hours. Then, ADH and EDC were added, and the reaction was carried out for 8-14 hours, during which the pH of the system was adjusted to maintain at 4.7-4.

8. The resulting reaction solution was then dialyzed at room temperature for 2-3 days, and after freeze-drying, polymer B was obtained. For each 30 mL of distilled water, add 1–5 g of zwitterionic acid, 0.2–1 g of acrylic acid, and 20–60 mg of initiator; the molar ratio is ADH:acrylic acid = 2:1; EDC:acrylic acid = 2:

1. The zwitterion is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propionic acid)ammonium hydroxide.

3. The method for preparing the injectable antibacterial and conductive hydrogel as described in claim 2, characterized in that the concentration of the NaClO solution is 1~10wt%; and the concentration of the concentrated hydrochloric acid is 6~12M.

Citation Information

Patent Citations

  • Intelligent conductive antibacterial hydrogel and preparation method thereof

    CN113201097A

  • Systems and methods for n-halamine-dopamine copolymers for high-performance, low-cost, and easy-to-apply antimicrobial coatings

    CN113227056A